Stress and and coping styles of special education teachers of children with mental retardation their implications to guidance - Bautista, Lilia S. (2006)
This study identified sources of stress among teachers of mentally retarded children, their coping strategies and styles, and effects on teachers' performance. The sample involved 52 teachers who cater to children with mental retardation in fourteen public and private schools in Quezon City. Questionnaires and interview schedules were utilized to gather research data. The results indicate that teachers' personality, family, and past experiences affect teacher's level of stress in the work places. The top five stressors are: welfare of children, food expenses, health condition of family and parents, communication gap, and no individuals wholesome recreation. Among the coping mechanisms employed are: watching television, talking to friends, praying/talking to God, going to malls, listening to music, indulging in hobbies and exercise, and going on out-of-town vacations. Findings could provide special education (SPED) teachers and school administrator's insights into the teaching-learning situation and enable them to cope with stressors, thus facilitating their special students' acquisition of knowledge and skills.
Keywords: Special education teachers -- Job stress; Adjustment (Psychology)